2011
DOI: 10.1007/s11242-011-9831-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Multigrid Methods for Numerical Solution of the Variably Saturated Flow Equation in Two Space Dimensions

Abstract: The need of accurate and efficient numerical schemes to solve Richards' equation is well recognized. This study is carried out to examine the numerical performances of the nonlinear multigrid method for numerical solving of the two-dimensional Richards' equation modeling water flow in variably saturated porous media. The numerical approach is based on an implicit, second-order accurate time discretization combined with a vertex centered finite volume method for spatial discretization. The test problems simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The computed results are depicted in Figure 4 which demonstrates that the process of infiltration can continue if there is a pool of water at ground surface maintained holding the pressure head for additional water at the soil surface. It is found that the best accuracy of the proposed method can reach up to 13 …”
Section: Steady-state Modeling Of Two-dimensional Subsurface Flow In mentioning
confidence: 99%
See 1 more Smart Citation
“…The computed results are depicted in Figure 4 which demonstrates that the process of infiltration can continue if there is a pool of water at ground surface maintained holding the pressure head for additional water at the soil surface. It is found that the best accuracy of the proposed method can reach up to 13 …”
Section: Steady-state Modeling Of Two-dimensional Subsurface Flow In mentioning
confidence: 99%
“…Nonlinear physical relationships can be described using soil-water characteristic curves [6][7][8]. Since the Richards equation is highly nonlinear and cannot directly provide an analytical solution, modeling flow process in unsaturated soils is usually based on the numerical solutions of the Richards equation [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…There have been efforts to develop or apply robust, scalable preconditioners for Richards' equation (Jenkins et al, 2001;Jones and Woodward, 2001), and high-quality software packages like PETSc provide access to a number of modern preconditioners as well as linear and nonlinear solvers (Balay et al, 1997). However, uniformly robust preconditioning techniques and nonlinear solver performance for Richards' equation for remains an open research topic (Juncu et al, 2011;Lipnikov et al, 2016).…”
Section: Linear and Nonlinear Solversmentioning
confidence: 99%
“…Since then, many authors have presented critiques of Richards' equation and existing solution techniques. A far-from-exhaustive sample includes (Forsyth et al, 1995;Tocci et al, 1997;van Dam and Feddes, 2000;Vogel et al, 2001;Kavetski et al, 2001a;Farthing et al, 2003b;Bause and Knabner, 2004;Manzini and Ferraris, 2004;D'Haese et al, 2007;Kees et al, 2008;Vogel and Ippisch, 2008;Juncu et al, 2011;Berninger et al, 2014;Lipnikov et al, 2016). Our intention here is not to repeat what those authors have written, rather it is to assess the state of the art, limitations, needs, and alternatives.…”
mentioning
confidence: 99%
“…Also, there are a number of effective solution approaches based on Newton's method, see for e.g. [42,43,44]. These methods exhibit a quadratic convergence rate but are very sensitive to initial solution approximations.…”
Section: Cell-centered Multigridmentioning
confidence: 99%